Printable carbon-based supercapacitors reinforced with cellulose and conductive polymers. (June 2022) - Belaineh, Dagmawi; Brooke, Robert; Sani, Negar; Say, Mehmet Girayhan; Håkansson, Karl M.O.; Engquist, Isak; Berggren, Magnus; Edberg, Jesper
Highlights: We have demonstrated a method for the sustainable, large-scale printing of supercapacitors using cellulose and conducting polymers. Printable conductive polymer, cellulose and carbon inks for supercapacitors provide superior characteristics compared to those previous. Minimal amount of PEDOT:PSS (10%) incorporated for optimal performance and cost effectiveness. Evidence to support PEDOT:PSS and cellulose act as a glue for the inks. Abstract: Sustainable electrical energy storage is one of the most important scientific endeavors of this century. Battery and supercapacitor technologies are here crucial, but typically the current state of the art suffers from either lack of large-scale production possibilities, sustainability or insufficient performance and hence cannot match growing demands in society. Paper and cellulosic materials are mature scalable templates for industrial roll-to-roll production. Organic materials, such as conducting polymers, and carbon derivatives are materials that can be synthesized or derived from abundant sources. Here, we report the combination of cellulose, PEDOT:PSS and carbon derivatives for bulk supercapacitor electrodes adapted for printed electronics. Cellulose provides a mesoscopic mesh for the organization of the active ingredients. Furthermore, the PEDOT:PSS in combination with carbon provides superior device characteristics when comparing to the previously standard combination of activated carbon and carbon black. PEDOT:PSS acts as a mixed ion-electron conducting glue, which physically binds activated carbon particles together, while at the same time facilitating swift transport of both electrons and ions. A surprisingly small amount (10%) of PEDOT:PSS is needed to achieve an optimal performance. This work shows that cellulose added to PEDOT:PSS-carbon enables high-performing, mechanically stable, printed supercapacitor electrodes using a combination of printing methods.